Aspirin-induced increase in intestinal paracellular permeability does not affect the levels of LPS in venous blood of healthy women. Issue 5 (July 2015) - Gnauck, Anne; Lentle, Roger G; Kruger, Marlena C
The presence of subclinical levels of LPS from Gram-negative bacteria, also referred to as endotoxin, in the circulation may induce a pro-inflammatory immune response that leads to the development of obesity and insulin resistance. Recent data indicate that high-fat meals may elevate circulating levels of LPS. However, it is currently unclear how the LPS transits from the gut lumen to the general circulation. We determined whether aspirin-induced damage of the small intestinal mucosa, evidenced by an increase in the paracellular permeability, allows greater transit of LPS into the systemic circulation. The 3-h cumulative excretion of lactulose was significantly increased after the consumption of aspirin solution relative to that after the consumption of an equal volume of water in 15 healthy women (median after aspirin 0.09% of dose vs. median after water 0.03% of dose; P  = 0.004). Dosage with aspirin also significantly increased the lactulose : mannitol ratio (median after aspirin 0.014 vs. median after water 0.005; P  = 0.017). However, serum LPS levels after the consumption of the aspirin solution were not significantly different from those after consumption of the control (plain water). Further, there was no correlation between body fat content and circulating levels of LPS.